The Effects of Concurrent Resistance and Endurance Training Follow a Specific Detraining Cycle in Young School Girls - Santos, Albano (2020)
The purpose of this study was to compare the effects of an 8-week training period of strength training alone (GR), or combined strength and endurance training (GCOM), followed by 12-weeks of de-training (DT) on body composition, power strength and VO2max adaptations in a schooled group of adolescent girls. Sixty-seven healthy girls recruited from a Portuguese public high school (age: 13.5+1.03 years, from 7(th) and 9th grade) were divided into three experimental groups to train twice a week for 8 wks: GR (n=21), GCOM (n=25) and a control group (GC: n=21; no training program). Anthropometric parameters variables as well as performance variables (strength and aerobic fitness) were assessed. No significant training-induced differences were observed in 1kg and 3kg medicine ball throw gains (2.7 to 10.8%) between GR and GCOM groups, whereas no significant changes were observed after a DT period in any of the experimental groups. Significant training-induced gains in CMVJ (8 to 12%) and CMSLJ (0.8 to 5.4%) were observed in the experimental groups. Time of 20m significantly decreased (GR: -11.5% and GCOM: -10%) after both treatment periods, whereas only the GR group kept the running speed after a DT period of 12 weeks. After training VO2max increased only slightly for GCOM (4.0%). No significant changes were observed after the DT period in all groups, except to GCOM in CMVJ and CMSLJ. Performing simultaneous strength and endurance training in the same workout does not appear to negatively influence power strength and aerobic fitness development in adolescent girls. Indeed, concurrent strength and endurance training seems to be an effective, well-rounded exercise program that can be prescribed as a means to improve initial or general strength in healthy school girls. De-training period was not sufficient to reduce the overall training effects.